Perubahan Pemahaman Mahasiswa Terhadap Makna Keimanan/ Kekafiran Ahli Kitab dengan Metode Tematik Digital Quran - M. Wildan Bin H.M. Yahya (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2022)
Muslim students view Ahli Kitab (followers of a non-Islamic religion) as kafir. As a result, they refuse non-Muslims to hold public positions because they are infidels. Whereas the Qur'an confirms that among the Ahli Kitab, some believe, are trustworthy, and are pious. The best solution is to develop a Quran-based Islamic Religious Education (PAI) learning model. The research aims to produce a digital Quran thematic learning model to understand the term Ahli Kitab in Al-Quran. Quasi R&D research method. Model testing at UNISBA and UPI. The themes discussed: the meaning of believing, the meaning of unbelievers, and the meaning of the People of the Book in the Al-Quran. The results of the study describes syntax model digital quran thematic and students' religious mindsets changed. At first, they associated faith and disbelief with religious identity. As for after college, they associate it with good and evil characters. According to the students, there are people of the Book who believe, but more are unbelievers. The implication is that the digital Quran thematic model is quite effective in changing the religious mindset of students.